IMPACT OF SOCIAL NETWORKS IN THE 21ST CENTURY AND THEIR IMPORTANCE FOR MARKETING IN THE DAIRY SUPPLY CHAIN (REMUNOM, 2026)
With the rapid advancement of digital technologies and the popularization of online platforms, social networks have become indispensable communication tools between companies and consumers. In the dairy production chain, YouTube has stood out as one of the strategic channels for dissemination, enabling not only brand promotion but also the dissemination of content focused on health and well-being. Furthermore, the study aligns with evidence that YouTube is a central channel for advertising ultra-processed foods, including dairy drinks from major brands, which reinforces the relevance of strategically analyzing the use of this platform by the dairy chain. This study analyzed 18 companies in the sector, divided into three categories (dairies, milk-based foods, and Whey Protein supplements), totaling more than 14,000 videos and over 3.6 billion views between 2018 and June 2025. Data were extracted using the YouTube Data Tools tool and analyzed using spreadsheet software and the Python programming language, allowing the identification of different communication patterns. The Clusters revealed four groups with distinct levels of digital performance, ranging from companies with low posting frequency and engagement, such as BatavoBrasil, with an average of only 2 videos/year, to high-performance ones, such as Growth TV, which averaged 261 videos per year and engagement rates exceeding 8% in likes and 0.26% in comments. The results indicate that companies with a more targeted focus on specific niches, such as sports nutrition supplements, show higher audience engagement, in contrast to traditional dairies, which still face difficulties in converting reach into meaningful interactions. Thus, the research highlights the need for more personalized digital strategies, focused not only on content volume but also on its relevance and suitability for the target audience.